Directed growth of horizontally aligned gallium nitride nanowires for nanoelectromechanical resonator Arrays - Henry, Tania; Kim, Kyungkon; Ren, Zaiyuan; Yerino, Christopher; Han, Jung; Tang, Hong X. (AMER CHEMICAL SOC, 2007)
We report the growth of horizontally aligned arrays and networks of GaN nanowires (NWs) as resonant components in nanoelectromechanical systems (NEMS). A combination of top-down selective area growth (SAG) and bottom-up vapor-liquid-solid (VLS) synthesis enables flexible fabrication of highly ordered nanowire arrays in situ with no postgrowth dispersion. Mechanical resonance of free-standing nanowires are measured, with quality factors (Q) ranging from 400 to 1000. We obtained a Young's modulus (E) of similar to 338 GPa from an array of NWs with varying diameters and lengths. The measurement allows detection of nanowire motion with a rotating frame and reveals dual fundamental resonant modes in two orthogonal planes. A universal ratio between the resonant frequencies of these two fundamental modes, irrespective of their dimensions, is observed and attributed to an isosceles cross section of GaN NWs.
Keywords: CHEMICAL-VAPOR-DEPOSITION; EPITAXIAL LATERAL OVERGROWTH; GAN NANOWIRES; MECHANICAL RESONANCE; CRYSTAL; SYSTEMS